Muhammadiyah dalam Menyikapi Sistem Kepemimpinan Nasional Saat Ini - Endang; Nur Efita Dewi (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This article discusses Muhammadiyah’s response to and position on Indonesia’s national leadership system in the contemporary era. As the largest modernist Islamic organization in Indonesia, Muhammadiyah plays a significant role in shaping political ethics, public morality, and national orientation in the life of the state. This study employs a qualitative approach based on library research by examining official Muhammadiyah documents, previous studies, and academic literature on prophetic leadership, Islamic civil society, and political ethics. The findings indicate that Muhammadiyah emphasizes a model of national leadership that is ethical, accountable, anti-corruption, and oriented toward public welfare. Muhammadiyah’s role in policy advocacy, civic political education, and the strengthening of democratic culture positions the organization as a strategic moral force within the national leadership ecosystem. These findings affirm that the values of Progressive Islam (Islam Berkemajuan) can contribute to the development of national leadership characterized by integrity and responsiveness to the nation’s challenges. Keywords: Muhammadiyah; National Leadership; Progressive Islam Abstrak Artikel ini membahas tentang respons dan posisi Muhammadiyah terhadap sistem kepemimpinan nasional Indonesia pada era kontemporer. Sebagai organisasi Islam modernis terbesar di Indonesia, Muhammadiyah memiliki peran signifikan dalam membentuk etika politik, moralitas publik, dan orientasi kebangsaan dalam kehidupan bernegara. Kajian ini menggunakan pendekatan kualitatif berbasis studi kepustakaan dengan menelaah dokumen resmi Muhammadiyah, penelitian terdahulu, serta literatur akademik mengenai kepemimpinan profetik, civil society Islam, dan etika politik. Hasil ini menunjukkan bahwa Muhammadiyah menekankan kepemimpinan nasional yang berkeadaban, akuntabel, antikorupsi, serta berorientasi pada kemaslahatan publik. Peran Muhammadiyah dalam advokasi kebijakan, pendidikan politik warga, serta penguatan budaya demokrasi menjadikan organisasi ini sebagai kekuatan moral strategis dalam ekosistem kepemimpinan nasional. Temuan ini menegaskan bahwa nilai-nilai Islam Berkemajuan dapat berkontribusi pada pembangunan kepemimpinan nasional yang berintegritas dan responsif terhadap tantangan bangsa. Kata Kunci : Muhammadiyah, Kepemimpinan nasional, Islam Berkemajuan